Développement et préservation des ressources naturelles, de la requalification à la valorisation du patrimoine : le cas de la réserve forestière d’Anjà à Madagascar - Narindra Hajatiana Rakotoarijaona (Belgeo)
Development occurs too often at the expense of both sustainability and the preservation of natural resources in a given territory. Drawing upon a territorial development approach, this article analyzes the case of a village in Madagascar, Anja, whose experience allows bringing these two issues together. The association of development, sustainability and preservation of natural resources, has been realized through requalification of the functions of Anja’s forest reserve. This dynamic emphasizes its immaterial and ideal value, linked to the identity, the history and the culture of the local population, and is based on the modification of its valorization and preservation dynamics. The aim of this article is to show that the heritage, as a specific resource to the territory, is a social construction. It also aims at highlighting that protection and development activities are governed by norms that are elaborated, accepted and legitimized at the local level. These activities involve a plurality of actors that include both public and private actors.